Circadian rhythm disruption impairs tissue homeostasis and exacerbates chronic inflammation in the intestine. Issue 11 (14th July 2017) - Pagel, René; Bär, Florian; Schröder, Torsten; Sünderhauf, Annika; Künstner, Axel; Ibrahim, Saleh M.; Autenrieth, Stella E.; Kalies, Kathrin; König, Peter; Tsang, Anthony H.; Bettenworth, Dominik; Divanovic, Senad; et al.
Abstract : Endogenous circadian clocks regulate 24‐h rhythms of physiology and behavior. Circadian rhythm disruption (CRD) is suggested as a risk factor for inflammatory bowel disease. However, the underlying molecular mechanisms remain unknown. Intestinal biopsies from Per1/2 mutant and wild‐type (WT) mice were investigated by electron microscopy, immunohistochemistry, and bromodeoxyuridine pulse–chase experiments. TNF‐α was injected intraperitoneally, with or without necrostatin‐1, into Per1/2 mice or rhythmic and externally desynchronized WT mice to study intestinal epithelial cell death. Experimental chronic colitis was induced by oral administration of dextran sodium sulfate. In vitro, caspase activity was assayed in Per1/2‐specific small interfering RNA–transfected cells. Wee1 was overexpressed to study antiapoptosis and the cell cycle. Genetic ablation of circadian clock function or environmental CRD in mice increased susceptibility to severe intestinal inflammation and epithelial dysregulation, accompanied by excessive necroptotic cell death and a reduced number of secretory epithelial cells. Receptor‐interacting serine/threonine‐protein kinase (RIP)‐3‐mediated intestinal necroptosis was linked to increased mitotic cell cycle arrest via Per1/2‐controlled Wee1, resulting in increased antiapoptosis via cellular inhibitor of apoptosis‐2. Together, our data suggest that circadian rhythm stability is pivotal for the maintenance of mucosal barrier function. CRD increases intestinal necroptosis, thus rendering the gut epithelium more susceptible to inflammatory processes.—Pagel, R., Bär, F., Schröder, T., Sünderhauf, A., Künstner, A., Ibrahim, S. M., Autenrieth, S. E., Kalies, K., König, P., Tsang, A. H., Bettenworth, D., Divanovic, S., Lehnert, H., Fellermann, K., Oster, H., Derer, S., Sina, C. Circadian rhythm disruption impairs tissue homeostasis and exacerbates chronic inflammation in the intestine. FASEB J. 31, 4707–4719 (2017). www.fasebj.org